2000
DOI: 10.1262/jrd.46.201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin Pro-.ALPHA.C as the Marker of Testicular Function in the Stallion.

Abstract: Abstract. Inhibin pro-αC is a precursor form of inhibin α-subunit. A large amount of inhibin pro-αC is secreted from testes in male animals, and it is considered to have an important role in the physiology of male reproduction. The purpose of this study was to determine the relationship between inhibin pro-αC and reproductive ability in the mature stallion. Peripheral blood samples were collected from normal stallions and anabolic steroid (nandrolone decanoate) treated stallions. Plasma concentrations of inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The level decreased in transitional and non-breeding seasons. Inhibin is secreted from the testis of stallion [ 12 , 16 ] and it can be the marker of the testicular function [ 13 ]. This clear seasonality in ir-inhibin is supported with previous findings in which increase in number of Sertoli cells and Leydig cell and smooth endoplasmic reticulum per testis has been shown during the breeding season of stallions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level decreased in transitional and non-breeding seasons. Inhibin is secreted from the testis of stallion [ 12 , 16 ] and it can be the marker of the testicular function [ 13 ]. This clear seasonality in ir-inhibin is supported with previous findings in which increase in number of Sertoli cells and Leydig cell and smooth endoplasmic reticulum per testis has been shown during the breeding season of stallions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibin levels are remarkably higher as compared with those of pregnant and cyclic mares [15][16][17]24] and stallions [33][34][35][36]. The inhibin subunits, namely inhibin ␣ and inhibin/ activin ␤ A and ␤ B subunits, were mainly localized to the interstitial cells of fetal ovaries from mid-to late gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Precursors of inhibin ␣ subunit have been reported to modulate FSH action (Schneyer et al, 1991) and have been found to play an important role in male reproductive physiology (Tuohimaa et al, 1993;Nagata et al, 2000).…”
Section: Plasma Concentrations Of Inhibin a Inhibin B And Inhibin Pmentioning
confidence: 99%
“…The present finding that inhibin ␣ subunit protein and its mRNA are present in Sertoli cells suggest that the cells may secrete inhibin ␣ subunit precursor, inhibin pro-␣C, and agrees with previous studies in other species (Fujimura et al, 1998;Nagata et al, 1998;Roberts et al, 1989;Kishi et al, 2000;Jin et al, 2001). Precursors of inhibin ␣ subunit have been reported to modulate FSH action (Schneyer et al, 1991) and have been found to play an important role in male reproductive physiology (Tuohimaa et al, 1993;Nagata et al, 2000).…”
Section: Concentrations Of Inhibin a Inhibin B And Inhibin Pro-␣c Imentioning
confidence: 99%